Severe Osteoporosis in an Adult Subject with RNU4-2 Gene Mutation: Severe Osteoporosis in an Adult Subject with RNU4-2 Gene Mutation - Peñafiel-Sam, Joshua; Valenzuela, Irene; Peris, Pilar (Calcified tissue international, 2025)
Recent studies have shown that RNU4-2 pathogenic gene variants are among the most frequent causes of monogenic neurodevelopmental disorders. We present an adult patient with a pathogenic variant in the RNU4-2 gene associated with the presence of severe osteoporosis. A 19-year-old male diagnosed with ReNU syndrome after years of extensive evaluation for a history of developmental delay, seizures, and hearing loss, was referred to our department for osteoporosis evaluation, presenting spontaneous humeral fracture at age 16, and a low-impact fibular fracture at age 8. Physical examination showed microcephaly, hypotelorism, thoracic asymmetry, and mild scoliosis, without bone tenderness. Extensive laboratory investigations, including hormonal study, excluded additional secondary causes of osteoporosis. Bone turnover markers were increased and dual-energy X-ray absorptiometry confirmed the presence of low bone mass (with a Z -score of − 1.9 in the lumbar spine, − 3.5 in the femoral neck, and − 3.7 in the total femur). Therapy with zoledronate acid was indicated. These observations suggests that ReNU syndrome includes bone disease in the clinical manifestations. Subjects with RNU4.2 mutations may present associated osteoporosis, indicating the need to evaluate the presence of bone disease in these individuals.